2006
DOI: 10.1253/circj.70.1116
|View full text |Cite
|
Sign up to set email alerts
|

Pravastatin Decreases Blood Pressure in Hypertensive and Hypercholesterolemic Patients Receiving Antihypertensive Treatment

Abstract: any patients with hypertension have concomitant hypercholesterolemia [1][2][3] and it has been reported that reductions in cholesterol levels correlate with lower diastolic blood pressure (DBP). 4 Further, experimental and clinical studies have demonstrated a strong correlation between high plasma cholesterol levels and impaired endothelium-dependent vascular relaxation. [5][6][7] These findings suggest that hypercholesterolemia may contribute to increased vascular reactivity and thereby contribute to systemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 50 publications
0
7
1
Order By: Relevance
“…Therefore, statins should be prescribed for Chinese CHD patients, besides their benefit of lipid lowering. [26][27][28][29][30] In this study, 82.2% of the participants received statin therapy, which was higher than a result from Japan (36.3%) 31 and from Hong Kong where a report showed that only 37% of participants received lipid-lowering drugs. 32 It is also higher than the results of small trials in China and other reports.…”
Section: Discussioncontrasting
confidence: 75%
“…Therefore, statins should be prescribed for Chinese CHD patients, besides their benefit of lipid lowering. [26][27][28][29][30] In this study, 82.2% of the participants received statin therapy, which was higher than a result from Japan (36.3%) 31 and from Hong Kong where a report showed that only 37% of participants received lipid-lowering drugs. 32 It is also higher than the results of small trials in China and other reports.…”
Section: Discussioncontrasting
confidence: 75%
“…In fact, systolic BP was significantly decreased after pravastatin treatment (from 141.2 ± 4.7 to 136.5 ± 5.3 mm Hg, P < 0.001), whereas no significant changes were noted in diastolic BP levels (from 81.3 ± 4.9 to 80.6 ± 5.1 mm Hg) [36]. It was reported recently that pravastatin exerts an additive "hypotensive" effect in hypercholesterolemic patients receiving antihypertensive therapy [37]. Notably, greater reductions in both systolic and diastolic BP were seen in patients with uncontrolled hypertension.…”
Section: Statins In Addition To Antihypertensive Treatmentmentioning
confidence: 83%
“…[25][26][27] Statins have several pleiotropic effects, including antiinflammatory and immunomodulatory, antithrombotic, and vascular effects, as well as their beneficial lipid-lowering effects. [28][29][30] In the clinical setting, it has been reported that statins improve LV function. Sola et al reported that atorvastatin therapy for 12 months increases LVEF, reduces the LV diameter, and improves several inflammatory markers in patients with nonischemic heart failure.…”
Section: Discussionmentioning
confidence: 99%